Atividade eletrocortical, senso de posição cervical e dor em sujeitos com cervicalgia mecânica submetidos ao conceito mulligan de tratamento - Oliveira, Cibele (2018)
Mechanical Cervicalgia can be defined as generalized pain in the cervical region, with a multifactorial etiology, and may promote functional alterations. As modifications of proprioceptive and sensorimotor deficits triggered by pain. In the scope of rehabilitation, aspects such as the sense of cervival position (CPS) and Quantitative Electroencephalography (EEGq) are able to evaluate motor and somatosensory processes related to musculoskeletal pain. The Mulligan Concept has deserved prominence from clinicians and researchers as tools to combat pain and improve functionality. Objective To verify the possible changes in the perception of pain, in the electrocortical activity of the central and parietal lobes; and in the sense of cervical position in individuals with Mechanical Cervicalgia, submitted to the SNAGS technique. Methodology This research is characterized as a Pre and Post-intervention Experimental Study, with the sample composed of 16 individuals with mechanical cervicalgia allocated in a single group. The SNAGS technique of the Mulligan Concept was used as a form of treatment. SPC was the pre and post-procedure analyzed standard; as well as the EEGq was used as a tool to analyze the electrocortical pattern before and after the immediate procedure, 5 and 10 minutes after the maneuver. Visual Analog Pain Scale (EVA) was also used to measure the level of pain in the research subjects. Results The sample consisted of 16 patients with mechanical cervicalgia (N = 16), Men = 4 and Women = 12, with mean age = 30.3 years. The mean reduction in pain percentage was 57.1%. Regarding SPC, the results indicated that there were no changes in pre and post- intervention conditions, the Relative Error (RE) measured in degrees, at the time Pre- intervention for the direct side was 3.8o; and for the left side it was 3.5o. At the time Post- intervention for the right side was 3.4o; and 3.3 ° to the left. Electroencephalic activity had a main effect between the conditions (pre, post, 5 and 10min) on Cz electrodes [F3,448 (p = 0.02)]; P3 [F23.370 (wt, 0.01)]; Pz [F48,481 (p, 0.01)]; P4 [F23,622 (p <0.01)]. Conclusion Our findings point to a modification of the electroencephalic activity in the alpha band in the motor and somatosensory areas between the pre and 10min moments after the application of SNAGs. However, the Mulligan maneuver did not cause immediate changes in SPC. Neck pain had a 57.1% reduction in pain according to the percentage of pain improvement.